2019
DOI: 10.18203/2320-1770.ijrcog20191926
|View full text |Cite
|
Sign up to set email alerts
|

Single embryo transfer and multifetal pregnancy reduction: perception and attitude of women seeking assisted reproduction in Nigeria

Abstract: Background: In-vitro fertilization (IVF) is associated with increased multiple pregnancy and its attendant complications. This study evaluates the attitude and acceptance of single embryo transfer (SET) and multifetal pregnancy reduction (MFPR) by clients assessing assisted reproduction in this region.Methods: A cross sectional survey of patients selected for IVF was conducted. Information on demography, knowledge of IVF procedure and their perception, attitude and acceptability of multiple pregnancy as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Howbeit, a previous study showed that despite recognizing the risks associated with higher-order multifetal pregnancy, infertile women still encourage transfer of multiple embryos and are less interested in SET or MFPR. [ 23 ] Furthermore, the satisfactory perinatal outcome observed despite increased incidence of preterm low births refers the need for the availability of high-quality neonatal care in facilities caring for IVF pregnancies. [ 21 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Howbeit, a previous study showed that despite recognizing the risks associated with higher-order multifetal pregnancy, infertile women still encourage transfer of multiple embryos and are less interested in SET or MFPR. [ 23 ] Furthermore, the satisfactory perinatal outcome observed despite increased incidence of preterm low births refers the need for the availability of high-quality neonatal care in facilities caring for IVF pregnancies. [ 21 24 ]…”
Section: Discussionmentioning
confidence: 99%